2009
DOI: 10.1016/j.cell.2009.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Cullin3-Based Polyubiquitination and p62-Dependent Aggregation of Caspase-8 Mediate Extrinsic Apoptosis Signaling

Abstract: Cell-surface death receptors such as DR4 and DR5 trigger apoptosis through a death-inducing signaling complex (DISC) that recruits the apical protease caspase-8. Apoptosis commitment requires efficient activation and autocatalytic release of caspase-8 into the cytoplasm to engage executioner caspases. While DISC recruitment initiates caspase-8 stimulation, full activation of the protease depends on further molecular aggregation events that are not fully understood. Here, we show that death receptor ligation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
295
3
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 545 publications
(312 citation statements)
references
References 46 publications
13
295
3
1
Order By: Relevance
“…The E3 ubiquitin ligase cullin 3 (CUL3)‐based polyubiquitination and p62‐dependent aggregation of caspase‐8 mediated extrinsic apoptosis signaling (Jin et al ., 2009). In prostate cancer cells, TRAIL induced caspase‐8 polyubiquitination, and the inhibition of caspase‐8 polyubiquitination restored caspase‐8 activation and apoptotic signaling (Fiandalo et al ., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The E3 ubiquitin ligase cullin 3 (CUL3)‐based polyubiquitination and p62‐dependent aggregation of caspase‐8 mediated extrinsic apoptosis signaling (Jin et al ., 2009). In prostate cancer cells, TRAIL induced caspase‐8 polyubiquitination, and the inhibition of caspase‐8 polyubiquitination restored caspase‐8 activation and apoptotic signaling (Fiandalo et al ., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Jin et al 103 recently reported that DR4/5 stimulation by Apo2L/TRAIL induces K63-linked ubiquitination of caspase-8. Caspase-8 is polyubiquitinated on the p10 subunit, which stabilizes the processed caspase-8 heterotetramer by recruiting the ubiquitin-binding protein p62.…”
Section: Fadd-mediated Dr Signaling: Fas/dr4/dr5mentioning
confidence: 99%
“…As caspase-8 is modified by both K48-and K63-linked polyubiquitin chains after Apo2L treatment, 103 it will be interesting to identify the physiological E2 used by the CUL3 ligase complex and to determine how the E2 binds ROC1 and orients the acceptor ubiquitin such that K63-linked ubiquitin chains are polymerized. A20 is recruited to the complex and mediates caspase-8 deubiquitination, 103 thus it is also possible that A20 facilitates caspase-8 K48 polyubiquitination. In addition, the identity of the adaptor protein that recruits caspase-8 to the CUL3/ROC1 complex is of intense interest.…”
Section: Fadd-mediated Dr Signaling: Fas/dr4/dr5mentioning
confidence: 99%
See 2 more Smart Citations